The trauma question - Luckhurst, Roger (New York : Routledge, 2008)
Roger Luckhurst introduces and advances the fields of cultural memory and trauma studies, tracing the ways in which ideas of trauma have become a major element in contemporary Western conceptions of the self.
The genealogy of a concept -- Trauma and modernity -- law of'nervous shock' -- Trauma in psychology 1870-1914 -- Trauma in the war ecology: shell shock -- Trauma and the politics of identity: Vietnam, Holocaust and abuse survivors -- Trauma in narrative fiction -- Beloved: a paradigmatic trauma fiction -- Stephen King's trauma gothic -- Mainstream fiction and traumatic anachrony -- W. G. Sebald: the last trawnatophile? -- My so-called life: the memoir boom -- Five elements towards the trauma memoir -- Memoir and the judicious truth -- Generating autofictions: Philip Roth, Herve Guibert, Kathryn Harrison --intrusive image: photography and trauma -- The fine art of trauma -- Aftermath aesthetics: Christian Boltanski, Gerhard Richter, Tracey Moffatt -- Beautiful books of atrocity: Sebastiao Salgado, Giles Peress, Luc Delahaye -- Flashbacks, mosaics and loops: Trauma and narrative cinema -- genealogy of the traumatic flashback -- Three trauma auteurs: Alain Resnais, Atom Egoyan, David Lynch -- Trauma and'post-classical' film since 1990.
Includes bibliographical references (p. [215]-233) and index.
Keywords: Medicine in Literature -- history; Medicine in Art -- history; Stress Disorders, Traumatic; Arts, Modern -- Psychological aspects; Psychic trauma in art; Psychic trauma -- Social aspects